From Mice to Men: Generation of Human Blastocyst-Like Structures In Vitro - Luijkx, Dorian; Shankar, Vinidhra; van Blitterswijk, Clemens; Giselbrecht, Stefan; Vrij, Erik (Frontiers in Cell and Developmental Biology, 2022)
Advances in the field of stem cell-based models have in recent years lead to the development of blastocyst-like structures termed blastoids. Blastoids can be used to study key events in mammalian pre-implantation development, as they mimic the blastocyst morphologically and transcriptionally, can progress to the post-implantation stage and can be generated in large numbers. Blastoids were originally developed using mouse pluripotent stem cells, and since several groups have successfully generated blastocyst models of the human system. Here we provide a comparison of the mouse and human protocols with the aim of deriving the core requirements for blastoid formation, discuss the models’ current ability to mimic blastocysts and give an outlook on potential future applications.